2021
DOI: 10.1186/s13104-020-05426-2
|View full text |Cite
|
Sign up to set email alerts
|

Prone positioning improves oxygenation and lung recruitment in patients with SARS-CoV-2 acute respiratory distress syndrome; a single centre cohort study of 20 consecutive patients

Abstract: Objective We aimed to characterize the effects of prone positioning on respiratory mechanics and oxygenation in invasively ventilated patients with SARS-CoV-2 ARDS. Results This was a prospective cohort study in the Intensive Care Unit (ICU) of a tertiary referral centre. We included 20 consecutive, invasively ventilated patients with laboratory confirmed SARS-CoV-2 related ARDS who underwent prone positioning in ICU as part of their management. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 22 publications
4
29
0
5
Order By: Relevance
“…Therefore, neonatal death is a concern for policymakers and researchers around the world. Baroni et al [ 7 ] investigated the neonatal mortality rates in Brazil, whereas Liu et al [ 8 ] and Abdul-Mumin et al [ 9 ] investigated the key reasons for neonatal death and preterm birth in China and Ghana. Regional investigations have identified that preterm birth, intrapartum complications and pneumonia (in case of China), and preterm birth complications and birth asphyxia (in case of Ghana) are the leading causes of neonatal deaths [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, neonatal death is a concern for policymakers and researchers around the world. Baroni et al [ 7 ] investigated the neonatal mortality rates in Brazil, whereas Liu et al [ 8 ] and Abdul-Mumin et al [ 9 ] investigated the key reasons for neonatal death and preterm birth in China and Ghana. Regional investigations have identified that preterm birth, intrapartum complications and pneumonia (in case of China), and preterm birth complications and birth asphyxia (in case of Ghana) are the leading causes of neonatal deaths [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of responders ranged from 9 to 77%. Seven studies provided data on static compliance of the respiratory system in supine preprone and in prone in intubated patients [ 3 ▪▪ , 35 , 37 , 42 , 45 48 ]. It significantly increased after a few hours in prone by 2 ml/cmH 2 O on average ( z = −2.68, P < 0.01) ( I 2 = 30%).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of aggregate data. Among 836 initially identified articles, 23 studies fulfilled the inclusion criteria and were included in the systematic review (flowchart shown in Figure 3) (7)(8)(9)(10)(11)(12)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The main characteristics of these studies are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%